1997
DOI: 10.1056/nejm199709183371203
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Term Trial of Tacrolimus Ointment for Atopic Dermatitis

Abstract: A short-term trial of tacrolimus ointment for atopic dermatitis Ruzicka, T.; Bieber, T.; Schopf, E.; Rubins, A.; Dobozy, A.; Bos, J.D.; Jablonska, S.; Ahmed, I.; Thestrup-Pedersen, K.; Daniel, F.; Finzi, A.; Reitamo, S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
1
17

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 493 publications
(189 citation statements)
references
References 17 publications
5
166
1
17
Order By: Relevance
“…Topical application of cyclosporine is not effective, 13 in contrast to the cyclic macrolide tacrolimus (FK 506), which proved to be effective in treating patients with AD. 14,15 Results of studies of the topical treatment of allergic contact dermatitis in pigs with other cytokine-inhibiting, antiinflammatory drugs, such as the ascomycin derivative (SDZ ASM 981), indicated that they might be effective in the topical treatment of skin disease in man. 16,17 Clearing of psoriatic lesions has been reported after topical application of 1% SDZ ASM 981 ointment under occlusion for 14 days (U.…”
Section: Resultsmentioning
confidence: 99%
“…Topical application of cyclosporine is not effective, 13 in contrast to the cyclic macrolide tacrolimus (FK 506), which proved to be effective in treating patients with AD. 14,15 Results of studies of the topical treatment of allergic contact dermatitis in pigs with other cytokine-inhibiting, antiinflammatory drugs, such as the ascomycin derivative (SDZ ASM 981), indicated that they might be effective in the topical treatment of skin disease in man. 16,17 Clearing of psoriatic lesions has been reported after topical application of 1% SDZ ASM 981 ointment under occlusion for 14 days (U.…”
Section: Resultsmentioning
confidence: 99%
“…For topical uses of tacrolimus that do not increase systemic blood concentration of the content, systemic tacrolimus levels were negligible when compared with using systemic agents (24,25). Therefore, it is suggested that unknown systemic factors may play a critical role in the local skin healing process, such as diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…23) Clinical trials have shown that short-term administration of topical tacrolimus is extremely effective and safe for controlling pruritus and skin inflammation. 11,12) In the mouse dermatitis model induced by repeated 2,4-dinitrofluorobenzene (DNFB) painting, tacrolimus significantly inhibited the scratching behavior, whereas dexamethasone had no effect. Tacrolimus possesses an anti-scratching activity that is not common in glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, reduction of pruritus was significantly higher for tacrolimus-treated patients than for vehicle-treated patients. 11,12) Therefore, we examined whether tacrolimus could produce an anti-pruritic effect in this model.…”
mentioning
confidence: 99%